2002
DOI: 10.1002/jcu.10089
|View full text |Cite
|
Sign up to set email alerts
|

Validity of sonographic screening for the detection of abdominal cancers

Abstract: The sensitivity of screening sonography was relatively high and the specificity was sufficient among our asymptomatic population. The present study suggests that the target organ for sonographic screening to detect curable cancers should be the kidneys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Complete diagnostic visualisation of kidneys by ultrasound occurs in 97.4% of cases, comparing favourably with 98.8% visualisation rates of the aorta in AAA screening [54, 55]. Mizuma et al and Filipas et al report an excellent sensitivity (82–83.3%) and specificity (98–99.3%) of ultrasound for detecting RCC in the general population as part of a screening intervention [56, 57]. The potential for false-negative results was not based on CT which is generally considered gold standard, but rather repeat ultrasound at a 1-year interval and follow-up via a registry and health records.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete diagnostic visualisation of kidneys by ultrasound occurs in 97.4% of cases, comparing favourably with 98.8% visualisation rates of the aorta in AAA screening [54, 55]. Mizuma et al and Filipas et al report an excellent sensitivity (82–83.3%) and specificity (98–99.3%) of ultrasound for detecting RCC in the general population as part of a screening intervention [56, 57]. The potential for false-negative results was not based on CT which is generally considered gold standard, but rather repeat ultrasound at a 1-year interval and follow-up via a registry and health records.…”
Section: Resultsmentioning
confidence: 99%
“…Several observational studies have been published on screening for RCC using ultrasound, however, none have been randomized in design, and all were published more than a decade ago [50, 5661] (Table 3). Mihara et al screened 219,640 asymptomatic Japanese individuals selected from the general population (age range 29–70 years) over a 13-year period [60].…”
Section: Resultsmentioning
confidence: 99%
“…None of the studies reported 95 per cent confidence intervals for point estimates of prevalence, despite the fact that this was an item on the quality assessment checklist (although this is readily calculable, given knowledge of the sample size). Three studies did not clearly state ultrasound criteria used to define a suspicious renal mass and three further studies included only solid (rather than complex cystic) masses in this definition. Five studies reported data on the prevalence of renal masses, but no histological data were available, so these studies were excluded from the analysis of the prevalence of histologically proven RCC.…”
Section: Resultsmentioning
confidence: 99%
“…It is anticipated that, in future, the development of non‐invasive modalities, such as measurement of urinary biomarkers, will allow improved discrimination between benign and malignant SRM (with further differentiation between indolent and aggressive RCC), enabling personalized treatment strategies and reducing overtreatment.These considerations may be offset further by the potential benefit derived from early detection of other malignancies within the renal fossa (including adrenal and upper urinary tract urothelial cell cancers, renal secondary metastases, renal carcinoid, sarcoma and lymphoma). Spouge and colleagues reported the prevalence of these combined malignancies as 0·2 per cent, whereas Mizuma et al , Malaeb and colleagues and Patel and co‐workers all reported a prevalence of 0·03 per cent. These rates vary considerably, and insufficient data were available for meta‐analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Observational studies evaluating screening for RCC using ultrasound have been conducted. However, none were randomised, and all were published more than a decade ago [11][12][13][14][15][16][17][18]. Owing to the relatively low prevalence of RCC in unselected asymptomatic individuals, a randomised controlled trial (RCT) sufficiently powered to detect an impact on survival would need to recruit hundreds of thousands of participants [11].…”
Section: Introductionmentioning
confidence: 99%